2011
DOI: 10.1007/s00134-011-2137-0
|View full text |Cite
|
Sign up to set email alerts
|

Social integration: an important factor for health-related quality of life after critical illness

Abstract: (Abstract length words 200)Objectives: To examine to what extent availability of social integration affect health related quality of life (HRQoL) in former Intensive Care Unit (ICU) patients and how it relates to corresponding findings in a general reference group.Design: Controlled, multicenter, prospective, explorative study. Setting and Patients:HRQoL data (SF-36) was collected from three combined medical and surgical intensive care units in the southeast of Sweden. Social integration was assessed by the Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Still, the effect of social integration was larger than age, sex and ICU-related factors. Social integration did not affect HRQOL in the general reference group (121). This previous research inspired us to study social support and its association with HRQOL in ICU survivors (116,117,121).…”
Section: Social Supportmentioning
confidence: 87%
“…Still, the effect of social integration was larger than age, sex and ICU-related factors. Social integration did not affect HRQOL in the general reference group (121). This previous research inspired us to study social support and its association with HRQOL in ICU survivors (116,117,121).…”
Section: Social Supportmentioning
confidence: 87%
“…Social function is only assessed by two questions in the Short Form-36 version 2 health survey (SF-36 v2) and is not assessed by the EQ-5D survey, two of the most common tools used to quantify quality of life [14, 62]. A study of 980 ICU survivors showed significant correlation between social integration level (measured by the Availability of Social Integration instrument) and SF-36 quality-of-life outcomes, with this correlation not present in matched controls [63]. Although the PROMIS outcome measures for social health have not yet been used in ICU survivors, findings from our systematic review highlight this domain for consideration in future research (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…As a special group, trauma patients have the greatest decrease in both physical and mental scores and only half of the survivors return to school or work 12 months after discharge (Myhren et al, 2010a(Myhren et al, , 2010b. Although many former ICU patients look after themselves 7-8 months after their stay in an ICU, fewer return to work and many have cognitive symptoms (reduced memory, concentration and planning ability) (Ågård et al, 2012) and decreased social integration (Orwelius et al, 2011), symptoms that could hinder return to work and reduce quality of life (Kvåle et al, 2003;Myhren et al, 2010aMyhren et al, , 2010b. Critical illness has a negative impact on employment, and patients may have a care requirement after discharge from an ICU (Kvåle et al, 2003, Griffiths et al, 2013.…”
Section: Everyday Lifementioning
confidence: 99%